Radiation intensity of base station antenna from Ad Hoc complex bessel functions series - Nieto Chaupis, Huber (2017)
In this paper, we have performed a closed-form calculation of the radiation pattern of a base station antenna by using Ad Hoc Bessel-Fourier expansion. Once the coordinates system is fixed, we proceed to derived the magnetic potential vector underlining the complex part which is subsequently expanded in a Bessel-Fourier series. Since the radiation intensity is proportional to the square of the polar component of electric field, we used the well-known relation vecE ≈ \vec{\nabla}× \vec{\nabla} × \vec{A} It gives capabilities to apply antenna data to the resulting closed-form expression for obtaining numerical estimations of the possible exposure levels. For this end, we measured the specific absorption radiation (SAR) to evaluate and discard possible effects of contamination by antenna radiation in the vicinity of the emission source. For a source of 2.0 GHz and 1.5 Vm-1, the estimation of SAR reaches up to 30 10-6 W Kg-1.